The Association Between Maternal–Fetal Medicine Physician Density and Pregnancy Outcomes - Kawakita, Tetsuya; Atwani, Rula; Hayasaka, Misa; Robbins, Lindsay; Saade, George (American Journal of Perinatology, 2025)
We sought to examine the association between maternal–fetal medicine (MFM) physician density and adverse pregnancy outcomes at the state level.This was a cross-sectional analysis of publicly available, state-level data from 2018 to 2021, including Natality, Multiple Cause-of-Death, and Fetal Death databases. The number of active MFM physicians per year was obtained for each state from the American Medical Association Masterfile. The primary exposure was the density of MFM per state, categorized into three groups: (1) low density (<30 MFM physicians per 100,000 live births), (2) moderate density (30–59 MFM physicians per 100,000 live births), and (3) high density (≥60 MFM physicians per 100,000 live births). Our primary outcome was maternal mortality during pregnancy and up to 42 days postdelivery. Our secondary outcomes were pregnancy-related mortality up to 365 days postdelivery and stillbirth. We calculated adjusted incident rate ratios (aIRR) and average marginal effect (AME) with 95% confidence intervals (95% CI) using multivariable negative binomial mixed effects regression models.Overall, there were 14,792,743 live births, 3,440 maternal mortalities, 4,980 pregnancy-related mortalities, and 90,848 stillbirths included. The median MFM density across states was 31.6 per 100,000 live births (interquartile range: 21.9–42.5). States with high MFM density had a reduced risk of maternal mortality (aIRR: 0.70; 95% CI: 0.58–0.85) and pregnancy-related mortality (aIRR: 0.83; 95% CI: 0.71–0.98) compared with states with low MFM density, corresponding to 7.29 (AME: 95% CI: 3.58–11.00) and 5.57 (AME: 95% CI: 0.74–10.40) less mortality per 100,000 live births, respectively. States with moderate MFM density had a similar risk of maternal mortality compared with low MFM density states (aIRR: 1.02; 95% CI: 0.87–1.20).High MFM-density states have a decreased risk of maternal mortality compared with low MFM-density states, suggesting a critical role of MFM in reducing maternal mortality.
Keywords: maternal death; maternal mortality; physician density; pregnancy-related mortality